2020
DOI: 10.3390/beverages6030050
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypropyl-β-Cyclodextrin as a Green Co-Solvent in the Aqueous Extraction of Polyphenols from Waste Orange Peels

Abstract: There is, to-date, an expanding interest concerning the use of cyclodextrins as green food-grade co-solvents in the aqueous extraction of polyphenols, however, data regarding polyphenol extraction from waste orange peels (WOP) are lacking. On this ground, hydroxypropyl β-cyclodextrin (HP-β-CD), a highly water-soluble cyclodextrin, was used to develop a simple and straightforward methodology for the effective recovery of WOP polyphenols. Process optimization by response surface showed that maximum total polyphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The tested CDs significantly differed regarding their ability to improve the functionality of OPEs; encapsulation with hydroxypropyl-β-CD (hpbCD) and randomly methylated β-CD provided comparable and the most significant benefits [8]. Similar findings have been reported by other authors who observed that positive effects on antioxidant activity were usually associated with improved solubility of formed inclusion complexes [7,9,10].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…The tested CDs significantly differed regarding their ability to improve the functionality of OPEs; encapsulation with hydroxypropyl-β-CD (hpbCD) and randomly methylated β-CD provided comparable and the most significant benefits [8]. Similar findings have been reported by other authors who observed that positive effects on antioxidant activity were usually associated with improved solubility of formed inclusion complexes [7,9,10].…”
Section: Introductionsupporting
confidence: 78%
“…They possess a relatively hydrophobic cavity and a hydrophilic external surface, which enables them to form inclusion complexes with structurally varied compounds. Therefore, they have been increasingly used as an eco-friendly means of recovering polyphenolic substances from complex matrices [7]. Available research suggests that, in addition to modifying extraction yields and physio-chemical properties of dry OPE, application of CD in OPE formulation can have significant impact on functional properties of obtained extracts, particularly on their antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
“…Such an outcome apparently contradicts recent examinations in which ultrasonication pretreatment significantly boosted polyphenol extraction using various means, including β-cyclodextrin [27], deep eutectic solvents [8], and hydroethanolic solutions [9]. However, negative effects have also been reported [28]. Therefore, it would be reasonable to presume that different plant matrices may behave in a different manner as a response to ultrasonication prior to performing stirred-tank extraction.…”
Section: Effect On the Flavonol And Anthocyanin Profilementioning
confidence: 86%
“…Green extraction procedures are good alternatives to classical organic phase separative methods. In this context, CDs are interesting agents to consider due to the hydrophobic nature of bioactive compounds [ 129 ], not only for the green chemistry process but also for the additional protection of the bioactive compound [ 130 ]. Several authors have reported interesting studies with CD-based materials.…”
Section: Applications Of Cyclodextrin-based Materials and Polymers In Food Sciencementioning
confidence: 99%